Cooperative Synthetic Inertia Control for Wind Farms Considering Frequency Regulation Capability - Shi, Qiaoming; Liu, Lei; Wang, Yongping; Lu, Yu; Zou, Qiang; Zhang, Qingwu; Liu, Hongqing (Frontiers in Energy Research, 2021)
To fully utilize the frequency regulation (FR) capability of wind turbines (WTs) and to avoid a secondary frequency drop caused by the rotor speed recovery, this paper firstly proposes an FR capability evaluation method for single and multiple wind farms based on the principle of equal rotational kinetic energy of WTs, and analyses the essence of cooperative rotor speed recovery for WTs. Based on these, a cooperative synthetic inertia control (CSIC) for wind farms considering FR capability is proposed. By introducing the cooperative coefficient, the CSIC can fully utilize the FR capability of WTs, maintain the fast response of WTs with synthetic inertia control, and reduce communication requirements for the wind farm control center. By directly compensating the auxiliary FR power of WTs, the CSIC realizes the cooperative rotor speed recovery for WTs between different wind farms, avoiding a secondary frequency drop and a complex schedule of rotor speed recovery for multiple WTs. Finally, the simulation results verify the effectiveness and feasibility of the proposed control.